Customer Engagement Levels: Analysis of Behaviour, Emotional, and Cognitive Dimensions - Santoso, Gilbert Moro; Agustini, M.Y. Dwi Hayu (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
Customer engagement is vital in fostering long-term relationships between businesses and their customers, particularly in the café industry, where personal interaction and atmosphere are essential to the experience. While existing studies have explored customer engagement in large-scale or digital settings, limited attention has been given to small, service-based businesses like independent cafés. This study addresses that gap by examining the level of customer engagement at Gerbang Coffee Culture, a local café known for its cozy environment but lacking a formal system to evaluate customer involvement. Using a quantitative approach, data were collected through questionnaires distributed to café visitors. Customer engagement was measured across three core dimensions: cognitive, affective, and behavioral. The results provide a comprehensive overview of how customers engage mentally, emotionally, and behaviorally with the café. The findings are expected to assist the café in designing more personalized and targeted marketing strategies based on customer interaction patterns. The study also contributes to the academic discourse by applying a multidimensional engagement framework in a real-world small business context. By integrating systematic measurement, cafés like Gerbang Coffee Culture can better understand their customers and strengthen relationships that support sustainable business growth.